A Novel 3D-Printed Head Holder for Guinea Pig Ear Surgery. Issue 9 (October 2021) - Valentini, Chris; Ryu, Young Jae; Szeto, Betsy; Yu, Michelle; Lalwani, Anil K.; Kysar, Jeffrey
Abstract : Background: Otologic surgery in guinea pig requires head immobilization for microscopic manipulation. Existing commercially available stereotaxic frames are expensive and impede access to the ear as they rely on ear bars or mouthpieces to secure the head. Method: Prototype head holders were designed using the Solidworks 2019 software and 3D-printed using Formlabs Form 2 Printers with photopolymer resin. The head holder consists of a C-shaped brace with adjustable radial inserts of 1/4-20 UNC standard screws with cone point tips providing head fixation for animals of various sizes. The C-shaped brace is attached to a rod that can be secured to a commercially available micromanipulator. The head holder design was tested during in vivo guinea pig experiments where their head motion with (n = 22) and without the head holder (n = 2) was evaluated visually through a stereotaxic microscope at 24× magnification during surgery. Results: The head holder design was easy to use and allowed for both nose cone administration of anesthesia and access to the ear for intraoperative auditory testing and manipulation. Functionally, the head holder successfully minimized head movement. Furthermore, harvested round window membranes evaluated at 72 hours following surgery showed precise perforations with the use of head holder. Conclusion: The novel 3D-printed head holder enables simultaneous access for nose cone administration of anesthesia and surgical manipulation of the ear and brain. Moreover, it provides a modular, intuitive, and economical alternative to commercial stereotaxic devices for minimizing head motion during small animal surgery.